Interaction of spatial and temporal integration in global form processing. - Aspell, J; Wattam-Bell, J; Braddick, O (2006)
The mechanisms by which global structure is extracted from local orientation information are not well understood. Sensitivity to global structure can be investigated using coherence thresholds for detection of global forms of varying complexity, such as parallel and concentric arrays of oriented line elements. In this study, we investigated temporal integration in the detection of these forms and its interaction with spatial integration. We find that for concentric patterns, integration times drop as region size increases from 3 degrees to 10.9 degrees , while for parallel patterns, the reverse is true. The same spatiotemporal relationship was found for Glass patterns as for line element arrays. The two types of organization therefore show quite different spatiotemporal relations, supporting previous arguments that different types of neural mechanism underlie their detection.